IMPROVING ANESTHESIOLOGICAL PROTECTION IN SURGICAL AND GYNECOLOGICAL PATIENTS DURING SIMULTANEOUS OPERATIONS - Kurbonov Navruzbek Zayniddin o’g’li, (JOURNAL OF NEW CENTURY INNOVATIONS, 2024)
This paper discusses reliable methods of anesthesia in simultaneous operations in surgical and gynecological patients. It evaluates the severity of surgical stress, the use of anesthesia techniques, the sedation component, artificial lung ventilation, anesthesia in surgery, and the impact of anesthetics and opioids on cognitive and psychomotor functions. The positive effects of combining epidural anesthesia with general anesthesia are also assessed.